Criteria for Determining Passenger Train Station Location in Bandar Lampung - Enggar Alviani; Kristianto Usman; Citra Persada; Chatarina Niken Dwi Wahyuni Setyo Budi Utami; Muhammad Karami (Universitas Islam 45, 2025)
the increasing number of passengers and the planned development of urban transportation infrastructure. However, the selection of station locations is a crucial aspect that requires careful consideration. This study aimed to identify the key criteria for determining passenger rail station locations in the city. The Delphi method and Analytic Hierarchy Process (AHP) were used to obtain structured expert assessments and to measure the priority of location criteria. The results indicated that accessibility was the criterion with the highest weight (0.480), followed by central activity areas (0.204), land use (0.167), and demand (0.148). Furthermore, the most influential sub-criteria were road networks (0.228), public transportation networks (0.156), and proximity to commercial and service centers (0.097). These results suggest that accessibility and proximity to central activity areas should be the primary considerations to improve mobility, reduce regional disparities, and support sustainable economic growth.